Grenada. Significant Achievements 2023 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
The Inter-American Institute for Cooperation on Agriculture (IICA), in collaboration with Australia Aid (AusAID), has taken significant steps to strengthen agricultural capabilities in the Caribbean region. Support was provided to institutions such as the Caribbean Agricultural Research and Development Institute (CARDI) and the Mirabeau Propagation Station of the Ministry of Agriculture to improve compost production at the commercial level. In addition, twenty-five women agricultural entrepreneurs were empowered through the Brown Gold Project, financed by AusAID, which included training in records management, post-harvest management and the use of QuickBook, as well as the development of a directory of support services available to agricultural entrepreneurs. In addition, the Last Mile Project, financed by the International Fund for Agricultural Development (IFAD), improved the data management capacity of the Ministry of Agriculture through a data collection application. These initiatives demonstrate the commitment of IICA and AusAID to strengthening agriculture in the Caribbean by promoting gender equity and sustainability in the sector.